Absorption of macronutrients and sodium by tomatoes submitted to normal and water deficient irrigation schemes using various concentrations of wastewater - DE SOUSA, Francielly Guieiro Gomes [UNESP]; DE CARVALHO, Renata Da Silva Cuba [UNESP]; DE MELO, Mara Rúbia Mendes [UNESP]; Filho, Hélio Grassi [UNESP] (My University, 2021)
The high worldwide demand for water use in economic development and domestic consumption has led to studies on the agricultural use of wastewater that can help minimize the problem of scarcity of this resource. This study aimed to evaluate the absorption of macronutrients and sodium from cultivated tomatoes, irrigated with wastewater, under normal and water deficient irrigation schemes. The experiment was conducted in a greenhouse, we used a drip irrigation system that was managed on the basis of evaporation from a Class A tank placed in the experimental area. Two irrigation depths were determined: 70 and 100% of the crop evapotranspiration, supply water, and four dilutions of domestic wastewater were used: 25, 50, 75, and 100%. We evaluated the absorption of macronutrients and sodium via chemical analysis of the leaves and fruits. Results showed that plants irrigated using the water deficit irrigation scheme absorbed more N, K, Mg, and S nutrients. However, the higher the percentage of wastewater used for irrigation, the higher the absorption of sodium by plants and fruits.
Absorção de macronutrientes e sódio pelo tomateiro submetido a irrigação com e sem déficit hídrico, utilizando diferentes concentrações de água residuária
Keywords: Domestic reuse; Irrigation management; Lycopersicon esculentum L; Nutrition